1980
DOI: 10.1007/bf02249793
|View full text |Cite
|
Sign up to set email alerts
|

Generation and processing of peripheral temperature signals in mammals

Abstract: A BST RACT. --Temperature transduction in peripheral cold receptors and processing of peripheral temperature signals in the spinal cord were studied in cats and rats. The temperature dependence of the generator potential is attributed to different temperature coefficients of an electrogenic Na-effiux and the passive Na-influx. Cold receptor activity and particularly its bursting pattern is considerably modulated by the local Ca-concentration, but the effect of elevated Ca-concentration is abolished by the ATPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 15 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…197 1 ;Iriki and Simon 1973) and skin temperature in our experiments. These changes may have stimulated cutaneous thermoreceptors (Hensel 1976;Pierau et al 1980;Sumins and Dubner 1981) to effect the changes in GC that we observed. Increases in central levels of adenosine (Laudignon et al 1991;Phillis et al 1987;VanWylen et al 1986;Ticho and Radulovacki 1991 ;Wang et al-1992) md (or) histamine (Sudhakaran et al 1979;Wada et id.…”
Section: Discussionmentioning
confidence: 68%
“…197 1 ;Iriki and Simon 1973) and skin temperature in our experiments. These changes may have stimulated cutaneous thermoreceptors (Hensel 1976;Pierau et al 1980;Sumins and Dubner 1981) to effect the changes in GC that we observed. Increases in central levels of adenosine (Laudignon et al 1991;Phillis et al 1987;VanWylen et al 1986;Ticho and Radulovacki 1991 ;Wang et al-1992) md (or) histamine (Sudhakaran et al 1979;Wada et id.…”
Section: Discussionmentioning
confidence: 68%
“…Stimulation of the nucleus raphe magnus has no effect on the spinal trigeminal neurones which respond to facial skin temperature (Dawson, Dickenson, Hellon & Woolf, 1981). There is evidence, however, that the scrotal skin temperature responsive neurones in the dorsal horn of the rat 316 SCROTAL THERMAL PATHWA Y AND RAPHE MAGNUS spinal cord are subject to tonic descending control (Pierau, Neya, Yamasato & Ulrich, 1980). Cooling the thoracic spinal cord, which reversibly blocks descending pathways, decreases the intrinsic firing rate of 60% of the scrotal temperature-responsive neurones in the spinal cord but the activity of the remaining temperature-responsive neurones is usually increased.…”
Section: Discussionmentioning
confidence: 99%
“…Three neurons were identified as inverse warm-reactive because the scrotal skin warming produced an inhibition and the cooling restored the intrinsic activity in the pre-warming period without inducing any facilitation (HELLON and MISRA, 1973a). Figure 3 shows the static activity of 29 neurons of the static and dynamic/ static warm-reactive type as a function of the scrotal temperature.In most of (PIERAU et al,1980).As is demonstrated in Fig.4…”
Section: Temperature Reaction Of Warm-reactive Dhnsmentioning
confidence: 73%